Multitarget Stool DNA Test Performance in an Average-Risk Colorectal Cancer Screening Population. (December 2019) - Bosch, L.J.W.; Melotte, V.; Mongera, S.; Daenen, K.L.J.; Coupé, V.M.H.; van Turenhout, S.T.; Stoop, E.M.; de Wijkerslooth, T.R.; Mulder, C.J.J.; Rausch, C.; Kuipers, E.J.; Dekker, E.; et al.
Abstract : INTRODUCTION: We set out to evaluate the performance of a multitarget stool DNA (MT-sDNA) in an average-risk colonoscopy-controlled colorectal cancer (CRC) screening population. MT-sDNA stool test results were evaluated against fecal immunochemical test (FIT) results for the detection of different lesions, including molecularly defined high-risk adenomas and several other tumor characteristics. METHODS: Whole stool samples (n = 1, 047) were prospectively collected and subjected to an MT-sDNA test, which tests for KRAS mutations, NDRG4 and BMP3 promoter methylation, and hemoglobin. Results for detecting CRC (n = 7), advanced precancerous lesions (advanced adenoma [AA] and advanced serrated polyps; n = 119), and non-AAs (n = 191) were compared with those of FIT alone (thresholds of 50, 75, and 100 hemoglobin/mL). AAs with high risk of progression were defined by the presence of specific DNA copy number events as measured by low-pass whole genome sequencing. RESULTS: The MT-sDNA test was more sensitive than FIT alone in detecting advanced precancerous lesions (46% (55/119) vs 27% (32/119), respectively, P < 0.001). Specificities among individuals with nonadvanced or negative findings (controls) were 89% (791/888) and 93% (828/888) for MT-sDNA and FIT testing, respectively. A positive MT-sDNA test was associated with multiple lesions ( P = 0.005), larger lesions ( P = 0.03), and lesions with tubulovillous architecture ( P = 0.04). The sensitivity of the MT-sDNA test or FIT in detecting individuals with high-risk AAs (n = 19) from individuals with low-risk AAs (n = 52) was not significantly different. DISCUSSION: In an average-risk screening population, the MT-sDNA test has an increased sensitivity for detecting advanced precancerous lesions compared with FIT alone. AAs with a high risk of progression were not detected with significantly higher sensitivity by MT-sDNA or FIT.